TINJAUAN YURIDIS PEMBERIAN REMISI TERHADAP NARAPIDANA TINDAK PIDANA KORUPSI DIKAITKAN DENGAN TEORI PEMIDANAAN - Cyntia Ayustika Fitria; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Remission or reduction of the criminal period which is a right for a prisoner or prisoner-assisted citizen is regulated in Law Number 12 of 1995 concerning correctional matters and regulated in Presidential Decree 174 of 1999 concerning remission. Whereas the granting of remission to corruption convicts is regulated in Government Regulation Number 99 of 2012 concerning the second amendment to Government Regulation Number 32 of 1999 concerning the requirements and procedures for the implementation of prisoners' rights Article 34 A paragraph 1.Since there has been a reduction in serving time (remission) in Indonesia there are problems that need attention, given the remission whether it will provide a deterrent effect for the perpetrators of the crime, especially for convicted corruption, plus the verdict of judges who tend to impose minimum criminal penalties on convicted criminal act of corruption.Granting remission to corruptors reaps a lot of opinions and criticisms. The granting of remission to corruptors is considered to be an improper and improper action to be given. Given that corruption crime continues to increase from year to year and the level of state losses are very large. This research will be prepared using the type of normative juridical research, namely research that is focused on examining the application of the rules or norms in positive law. The approach used in this research is to use a normative approach, namely library law research. The results of the research conducted by the author are, firstly for the application of remission based on Government Regulation Number 99 of 2012, and to find out whether or not the relevant remission of corruption is based on criminaltheory.Keywords: Granting Remission - Corruption Crime - Criminal Theory